Impact Sedimentation To Community Structure Macrozoobenthos In Segara Anakan Lagoon - Mohd Khairul Amri, Kamarudin; Ireana Yusra, Abdul Fatah; Muhammad Barzani, Gasim; Hafizan, Juahir (2018)
Change of structure community of Macrozoobenthos due to sedimentation has apparently contributed to a reduction of the quality of the aquatic environment, particularly in Segara Anakan Lagoon. This study aims to determine the extent to which the effects of sedimentation and nutrients in the Segara Anakan Lagoon on macrozoobenthos community structure. The method used in this study surveys. Primary data collected are nutrients, macrozoobenthos, sedimentation rate and secondary data. The results showed that the rate of sedimentation in the dry and rainy season was 0.067 to 2 m/s and 1.61 to 2.00 m/s respectively. Balanus sp, Melanoides sp, Corbicula sp, Polychaeta sp., Thiara sp. were dominance in the dry season, while Corbicula sp, Melanoides sp, Thiara sp, Tarebra sp, Balanus sp, Polychaeta sp. and Barbatia sp. were dominance in the rainy season.